1987
DOI: 10.1203/00006450-198711000-00016
|View full text |Cite
|
Sign up to set email alerts
|

Lactate Metabolism of Isolated, Perfused Fetal, and Newborn Pig Hearts

Abstract: ABSTRACT. The role of lactate as an energy substrate in fetal (0.9 gestation) and newborn (2 day old) hearts was investigated in isolated, perfused hearts. Perfusions were performed with Krebs-Henseleit buffer supplemented with , glucose (5 mM) in combination with ~ar~in~concentrations of lactate. Isolated working heart ~erfusions. in which the u heart ejects the buffer at controlled pressure, were carried out with glucose (5 mM) alone and with glucose (5 mM) and lactate (5 mM) combined. With glucose as sole s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
56
0

Year Published

1993
1993
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 14 publications
1
56
0
Order By: Relevance
“…We have also observed that pyruvate oxidation activity in heart homogenates from mice increases acutely after weaning (Itoi T, unpublished observations). Although glucose oxidation rates are low in immature hearts, lactate oxidation rates can be substantial (3,8). This may be related to the amount of specific isoforms of LDH in the heart.…”
Section: Source Of Atp Production In Newborn Hearts R ------------------mentioning
confidence: 99%
See 2 more Smart Citations
“…We have also observed that pyruvate oxidation activity in heart homogenates from mice increases acutely after weaning (Itoi T, unpublished observations). Although glucose oxidation rates are low in immature hearts, lactate oxidation rates can be substantial (3,8). This may be related to the amount of specific isoforms of LDH in the heart.…”
Section: Source Of Atp Production In Newborn Hearts R ------------------mentioning
confidence: 99%
“…Although glucose oxidation is a prominent source of ATP production in adult hearts, glucose oxidation rates are very low in the newborn heart (3). In contrast, lactate, which can be readily oxidized by fetal hearts (7,8), is a major source of ATP production in 1-and 7-d-old rabbit hearts (3). In adults, lactate oxidation is thought to be less important as a source of ATP production, although higher concentrations of lactate can reduce the rate of release and oxidation of fatty acids (9,10).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Lactate and other monocarboxylates not only serve the major carbon sources for fatty acid synthesis but also are utilized as a metabolic energy source in various fetal tissues, such as the porcine heart [34], rat brain [35], and ovine liver [36]. The H + gradient-dependent lactate transport occurs in the brush-border membrane of the trophoblast in rat [37] and human placentas [5,7,8] and in the basal plasma membrane of the trophoblast in humans [5,38].…”
Section: Subcellular Localization Of Mct1 and Mct4 And The Transfer Omentioning
confidence: 99%
“…However, very soon after birth the heart shifts to fatty acids as the major fuel substrate, coincident with the mitochondrial biogenic response (Figure 1 and refs. [5][6][7][8]. The level of glucose oxidation also increases (8).…”
Section: Brief Overview Of Cardiac Fuel and Energy Metabolismmentioning
confidence: 99%